Efektivitas Augmented Reality (AR) pada Konsep Pembelajaran IPA Sekolah Dasar: Augmented Reality - Ifa Safira; Abdurrachman Rahim; Pricilia Indah Palangi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The Effectiveness of Augmented Reality (AR) in Elementary School Science Learning Concepts. This study aims to determine the effectiveness of the use of Augmented Reality learning media on the mastery of the science concept of fifth grade elementary school students at SD Shipyard IV. The method in this research is experimental. The research population was all fifth grade elementary school students in Shipyard IV-VI with a total of 105 students and 39 students as a sample. The sampling technique used purposive sampling. Treatment using Augmented Reality learning media for 6x meetings. Data collection was carried out by the test method. The test instrument consisted of 30 multiple choice questions on environmental material. The use of Augmented Reality learning media can easily visualize the addition of virtual objects into a real environment and help students imagine objects from various points of view thereby improving the learning process and student learning outcomes. The increase can be seen from the results of the N-Gain test in the pretest and posttest which were 0.74 which was included in the high category, and the Paired sample T-test obtained a significant level of 0.00 < 0.05 (effective). The results of the study show that there is effectiveness in the application of Agumented Reality media to the mastery of science concepts in fifth grade elementary school students at SD Shipyard IV.